Muatan Pengembangan Sikap Pluralisme Agama dalam Buku Pendidikan Agama Katolik Kelas 12 Kurikulum 2013 - Widyawati, Fransiska; Bule, Oswaldus (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2024)
Intolerance, radicalism, and violence towards groups with divergent ideas continue to be a concerning issue in Indonesia. One reason is that the religious education paradigm offered does not promote a mindset of religious pluralism. This study aims to examine the substance of religious pluralism education in Catholic Religious Education (PAK) designed for Senior High School (SMA/SMK) students following the 2013 Curriculum. This study employs a qualitative methodology, utilizing text analysis techniques. This study discovered that using PAK content significantly contributes to cultivating a religiously pluralistic mindset among students. The pluralistic content in the resources, objectives, competencies, procedures, and tasks for students enhances and reinforces the students' pluralist nature. If PAK is effectively developed, pupils have the potential to become individuals who embrace pluralism, engage in dialogue, and possess an open mindset. Intoleransi, radikalisme dan kekerasan terhadap kelompok yang memiliki keyakinan berbeda masih menjadi masalah memprihatinkan di Indonesia. Salah satu penyebabnya adalah karena model pendidikan agama yang diberikan tidak mendukung sikap pluralisme beragama. Penelitian ini bertujuan untuk menganalisis muatan edukasi pluralisme beragama dalam Materi Pendidikan Agama Katolik (PAK) bagi siswa SMA/SMK Kurikulum 2013. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis teks. Penelitian ini menemukan bahwa materi PAK memiliki edukasi yang kuat untuk membentuk sikap pluralisme agama bagi siswa. Hal ini ditemukan dalam materi, tujuan, kompetensi, proses dan penugasan bagi para siswa yang mengandung muatan pluralisme dan memperkuat karakter siswa yang pluralis. Jika PAK dikembangkan dengan baik maka siswa dapat menjadi insan yang pluralis, dialogal dan terbuka.